Factors influencing oral cancer screening preferences in patients attending Tertiary Care University Oral Health Clinic. (23rd November 2021) - McGowan, B; Grace, H; Beste, D; Frey, S; Bridges, J; Sun, J; Nair, RG
Abstract: Background: Understanding factors that influence patients' preferences towards oral cancer (OC) screening is imperative to provide high‐quality evidence‐based OC screening interventions that can be targeted for population‐level uptake. This study determined adult patients' knowledge and awareness of OC, and how health behaviours influenced their preferences towards OC screening. Methods: This cross‐sectional study used a 42‐point questionnaire, between February and May 2020 using a combination of in‐person and telephone interviews. Chi‐square test and multiple logistic regression analysis were applied to confounding factors that returned statistical significance against OC knowledge and awareness. Significance of P  < 0.05 was accepted. Results: Sixty‐eight (38.6%) participants out of a total 176 had good knowledge of OC and 89 (50.6%) had good awareness. A total of 31.8% reported preference for OC screening by a general dental practitioner (GDP) over a general medical practitioner (GMP). Majority (72.7%) reported acceptance of OC screening at their next GDP visit. Ages 56–70 (OR = 0.357, 95% CI) and previous smokers (OR = 0.336, 95% CI) significantly influenced screening preferences. Knowledge of risk factors did not significantly influence OC screening preferences (χ 2  = 3.178, P  = 0.075). Conclusions: Significant gaps in OC knowledge, screening and role of GDPs exist with smoking history and age influencing OC screening preferences.